Chemical investigation on Indonesian marine sponge Mycale phyllophila - Hertiani, Triana; Edrada, Ru Angelie; Van Soest, Rob W.M.; ., Sudarsono; Muller, Werner E.G.; Proksch, Peter (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2009)
Chemical investigation on marine sponge Mycale phyllophila collected from Bali, Indonesia has been performed. This study was aimed to isolate and to identify structures of the sponge secondary metabolites as well as to test their cytotoxic activity on mouse lymphoma cell line L5178Y.The sponge extract was fractionated by liquid-liquid partition followed with a vacuum liquid chromatography method. Structure elucidation was performed on the basis of extensive spectroscopic analysis involving one and two dimensional NMR spectroscopy as well as mass spectrometry. Cytotoxicity was tested on mouse lymphoma cell line L5178Y by using the microculture tetrazolium (MTT) assay. This study found a mixture of 5-pentadecyl-1H-pyrrole-2-carbaldehyde and (6’E)-5-(6’pentadecenyl)-1H-pyrrole-2-carbaldehyde as major constituents of the sponge extract. Those compounds were expected to be the active constituent to show growth inhibition of mouse lymphoma cell line (L5178Y) in vitro.Key words : Mycale phyllophila, cytotoxic agent, NMR spectroscopy.